Tahiti & French Polynesia 2025 - Carillet, Jean-Bernard; Brash, Celeste (Lonely Planet guidebooks., 2025)
Lonely Planet's local travel experts reveal all you need to know to plan the trip of a lifetime to Tahiti & French Polynesia. Discover popular and off the beaten track experiences from visiting one of the world's most important ancient Polynesian places of worship: Mara Taputapuatea, to swimming with manta rays at La Ferme, and relaxing on the beautiful palm-fringed Temae Beach.